Flow and heat transfer over stretching or shrinking wedge in hybrid nanofluids using Tiwari-Das Model / Muhammad Shamil Adli Sahrin, Naqib Arif Abdul Aziz and Fatimah Hazirah Abu Hassan Ashaari - Sahrin, Muhammad Shamil Adli; Abdul Aziz, Naqib Arif; Abu Hassan Ashaari, Fatimah Hazirah (2023)
This study intends to discover the flow and heat transfer over stretching or shrinking wedge in hybrid nanofluid. Yacob et al. (2011) conducted a study on steady two-dimensional boundary layer flow past a static or a moving wedge immersed in nanofluids. They have numerically studied the Falkner-Skan problem for a static or moving wedge immersed in nanofluids. They obtained triple solution in stretching/shrinking parameter in nanofluids. Motivated by the growing trend of hybrid nanofluids, which are driven by heat and flux transfer across moving surfaces and have a wide range of industrial applications. Therefore, we will extend the paper of Yacob et al. (2011), but in hybrid nanofluid to study the effect of wedge parameter, and stretching or shrinking parameter on the velocity, temperature profiles, local skin friction coefficient and local Nusselt number. The governing equations were transformed into non-linear ordinary differential equations using a similarity transformation, which were then solved using the bvp4c function in MATLAB.